Pengaruh Penggunaan Akun Media Sosial Instagram USS Feeds terhadap Pemenuhan Informasi - Alfaddil, Andre; Andary, Ria Wury (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
Social media has become the primary source of information for the younger generation, replacing the role of conventional media. This study aims to analyze and determine the effect of the use of USS Feeds' Instagram social media accounts on the fulfillment of information for Communication Science students of the University of Medan Area for the 2021 academic year. Therefore, the problem is focused on the influence of the use of USS Feeds' Instagram social media accounts on information fulfillment. So that to solve this problem, references such as New media theory, agenda setting, and Uses and Gratifications are used. The data were collected through a Likert scale and questionnaire and analyzed quantitatively and with descriptive explanations. The results showed that the use of the @ussfeeds account had a positive and significant effect on the fulfillment of student information, with a significance value of 0.000 < 0.05 and an R² of 82.2%. These findings support the theory of Uses and Gratifications and Agenda Setting, which explains that students actively choose media according to their needs and that media also influences their perception of important issues. This study recommends strengthening digital literacy so that students are more critical in receiving information from social media.